Path Analysis on the Factors Affecting People’s Behavior in HIV/AIDS Countermeasure on People Living with HIV/AIDS (PLWHA) in Solo Plus Peer Support Group, Surakarta - Kingkin Adita; Argyo Demartoto; Eti Poncorini Pamungkasari (Masters Program in Public Health, Sebelas Maret University, 2017)
Background: HIV or Human Immunodeficiency Virus is a virus that infects white blood cells so the person’s immunity declining thus causing it to become AIDS. HIV/AIDS countermeasure is far more effectively done by people living with HIV/AIDS (PLWHA) accompanied by good attitude and peer support, family, and health workers, Regional AIDS Countermeasure Commission, perceived behavioral control, and positive intention. The study aimed to analyze factors affecting the attitude in HIV/AIDS countermeasure on PLWHA in Solo Plus Peer Support Group (PSG) Surakarta with theory of planned behavior application. Subjects and Methods: The study design was analytic observational with cross sectional study approach. The location of the study was Solo Plus Peer Support Group Surakarta. Time of study was from January-February 2017. There was a total of 100 PLWHA as the sample, and the study employed purposive sampling technique. The dependent variable was the attitude towards HIV/AIDS countermeasure. The independent variables were the attitude, peer, family, health workers, Regional AIDS Countermeasure Commission support, perceived behavioral control and their intention. The variables were measured with questionnaires. Data analysis technique used was path analysis.Results: HIV/AIDS countermeasure attitude affected by intention(b=0.27; SE=0.10; p=0.012), peer support (b=0.26; SE=0.14, p= 0.066), AIDS Countermeasure Commission support (b=0.10; SE=0.10; p= 0.321), health workers support (b= 0.25, SE= 0.14, p= 0.073) and perceived behavioral control (b=0.23; SE=0.13; p=0.065). Intention affected by attitude (b=0.28; SE=0.15; p=0.059), peer support (b=0.29; SE= 0.13; p= 0.026), family support (b=0.16; SE=0.09, p= 0.090) and perceived behavioral control (b=0.21; SE= 0.11; p= 0.090).Conclusion: HIV/ AIDS countermeasure behavior was very much affected by the intention, peer support, AIDS Countermeasure Commission support, health worker support, and perceived behavioral control. Their intention was affected by attitude, peer support, family support, and perceived behavioral control.Keywords: HIV, PLWHA, TPB, countermeasure.Correspondence: Kingkin Adita. Masters Program in Public Heath, Sebelas Maret University, Surakarta. Email: kingkin_adita@gmail.com. Mobile: 085726389133.Journal of Health Promotion and Behavior (2017), 2(1): 41-54https://doi.org/10.26911/thejhpb.2017.02.01.04